## Expanding (x+3)(x-5) to Standard Form

In mathematics, the **standard form of a quadratic equation** is expressed as **ax² + bx + c**, where a, b, and c are constants and a ≠ 0. To express the given expression (x+3)(x-5) in standard form, we need to expand and simplify it.

### Expanding the Expression

We can use the **FOIL method** to expand the expression:

**F**irst: x * x = x²**O**uter: x * -5 = -5x**I**nner: 3 * x = 3x**L**ast: 3 * -5 = -15

Combining the terms, we get:

(x+3)(x-5) = x² - 5x + 3x - 15

### Simplifying the Expression

Now we can combine the like terms:

x² - 5x + 3x - 15 = **x² - 2x - 15**

### Final Answer

Therefore, the standard form of (x+3)(x-5) is **x² - 2x - 15**.